Adopting Research and Information Dissemination as a Mechanism for Mitigating Farmers/Pastoralists Conflicts in the Middle Belt States Of Nigeria - Taazenga, Tarwa Edward (MiddleBelt Journal of Library and Information Science, 2016)
Persistent conflicts between farmers and pastoralist in the Middle Belt Zone have taken a more dangerous dimension in recent times. Deaths, wanton destruction of properties as well as displacement of people from their communities have become the order of the day. This situation is not only economically dangerous to the people of the zone, but has also posed serious challenges to the political stability of the country, making governance difficult. The aim of this paper is to suggest to stake holders in the business of conflict resolution and peace building that the option of, “research and information dissemination” should be adopted as a mechanism for curbing this persistent upheavals, between farmers and pastoralists in the region. Towards accomplishing this desire, the paper discussed key words contained in the discussion and as well highlighted on key components of an empirical research in relation to farmers/pastoralists conflicts. It sums up that research and information dissemination provides more reliable information and as well forms a formidable platform for mitigating farmers/pastoralists conflicts in the Middle Belt States of Nigeria. Hence the paper explains further that information obtained as a result of this exercise shall be devoid of gossips and more authentic to be used in addressing this ugly situation.